NGUDI SEJAHTERA VILLAGE OWNED ENTERPRISES (BUMDES) DEVELOPMENT STRATEGY IN IMPROVING THE WELFARE OF THE NGUNUT VILLAGE COMMUNITY - Novitasari, Rika; Harsanti, Tikka Dessy (Gapenas Publisher, 2024)
Village-Owned Enterprises (BUMDes) are business entities established and owned by the Village with one of the aims of increasing the village's original income. The Tulungagung Regency Government has implemented facilities for the formation of Village BUMs in 257 villages which are divided into the advanced category of 41 Village BUMs. One of the villages in Tulungagung Regency which has quite large local potential is Ngunut village. Along with the increasing number of local industrial sectors in Ngunut Village that have economic value, BUMDes in Ngunut village are still not being utilized optimally by some village communities. The aim of the research is to find out how the strategy for developing Ngudi Sejahtera Village-Owned Enterprises is to improve community welfare in Ngunut Village, Ngunut District, Tulungagung Regency. The type of research in this research is empirical legal research or sociological legal research and can also be called field research. The approach method used in this research is a sociological juridical approach. The village government's efforts in developing an independent village strategy are by increasing sales of Ngunut Village community products, namely the production of agricultural equipment. In addition, efforts are being made to improve production quality by establishing relationships between BUMDes Ngudi Sejahtera and the Ministry of Industry